ULTRA-SHORT PRESENTATION IN VIRTUAL ENGLISH PUBLIC SPEAKING OF NON-ENGLISH MAJOR STUDENTS - Hilaliyah, Iil; Zaitun, Zaitun (Universitas Tanjungpura, 2024)
This research is aimed to introduce one technique of performing English public speaking to non-English major students called Ultra-Short Presentation. There were a number of 34 non-English students of Faculty of Education, Universitas Muhammadiyah Jakarta, participated in this study, registered as the second semester in the academic year of 2022/2023. The method applied in this study was quantitative approach with true experimental design. In collecting the data, both pre and post-tests of performing public speaking virtually were used. Each student